2020
DOI: 10.1016/j.heliyon.2020.e03608
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to low doses of dichlorodiphenyltrichloroethane impairs proliferative response of thymic lymphocytes to Concanavalin A in rats

Abstract: The aim of the research was to study formation of thymic lymphocytes proliferative response to T cell mitogen Concanavalin A in 7, 42, and 70 days-old male Wistar rats developmentally exposed to low doses of endocrine disruptor dichlorodiphenyltrichloroethane (2.90 AE 0.13 μg/kg body weight). The thymus of the exposed rats did not show morphological abnormalities. Exposure to the endocrine disrupter was found to alter age-dependent changes of thymic lymphocyte proliferative activity and attenuate proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…It is known that the functional maturation and structural development of the immune system are extremely sensitive to external influences. It has been shown that prenatal exposure to such influences not only affects morphogenetic processes in the central and peripheral organs of immunity, but also disconnects ерese processes [12,16]. The spleen is the largest peripheral organ of immune defense, which in ontogenesis is exposed both to the influence of the central organs of the immune system and to the impact of various factors that directly interfere with the development of lymphoid formations and stromal components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the functional maturation and structural development of the immune system are extremely sensitive to external influences. It has been shown that prenatal exposure to such influences not only affects morphogenetic processes in the central and peripheral organs of immunity, but also disconnects ерese processes [12,16]. The spleen is the largest peripheral organ of immune defense, which in ontogenesis is exposed both to the influence of the central organs of the immune system and to the impact of various factors that directly interfere with the development of lymphoid formations and stromal components.…”
Section: Discussionmentioning
confidence: 99%
“…DDT readily crosses the placental barrier and is excreted in milk, so its possible effects on organ development are of great concern [10,11]. We have previously demonstrated that developmental exposure to low doses of DDT resulted in changes in the rate of thymic growth and preservation of the functional maturation of thymic lymphocytes [12,13]. Damage to the central organs of immunity by an endocrine disruptor can probably lead to dysfunction of lymphocytes in peripheral lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%
“…Таким образом, оказывается, что тимус крыс, подвергшихся воздействию эндокринного дисраптора, был более ювенильным по сравнению с контрольной группой. Ранее мы показали, что пролиферативный ответ на Т-клеточный митоген Конканавалин А у препубертатных и пубертатных крыс был адекватен возрасту и не отличался от контроля, но после полового созревания, в возрасте 10 нед, значительно снижался [20]. Известно, что сниженный пролиферативный ответ на митоген свидетельствует о функциональной незрелости лимфоцитов, характерной для неонатального периода онтогенеза [21].…”
Section: Discussionunclassified
“…Thus, it appears that the thymus of rats developmentally exposed to the endocrine disruptor DDT was more juvenile compared to the age control. In our previous research, we investigated the development of the proliferative response of thymic lymphocytes to T-cell mitogen Concanavalin A in rats with the same regimen of prenatal and postnatal exposure to DDT and found that the response in prepubertal and pubertal rats was adequate to age control, but after puberty—at the age of 10 weeks—it showed a significant decrease [ 43 ]. An insufficient proliferation response to mitogen is known to indicate functional immaturity of lymphocytes typical for the neonatal period of ontogeny [ 44 ].…”
Section: Discussionmentioning
confidence: 99%